Sistem Otomatisasi Pengendalian Kelembaban menggunakan Sensor DHT21 dan Modul Peredup Arus Bolak-Balik (AC Light Dimmer) - Mansyur, Syaiful; Harahap, Akhirul April (CV. IRA PUBLISHING, 2025)
This study analyzes an environmental control system based on an AC Light Dimmer, integrating ADC values, AC voltage, and RPM for drying applications. The results reveal a strong linear relationship between ADC values and AC voltage, with blower RPM increasing proportionally to the voltage. The system successfully reduced humidity from 60% to 26.3% and increased temperatures from 35.6°C to 50.6°C automatically via DHT21 sensors. While the ADC performed well, potential saturation at high voltages requires careful design consideration. Overall, the microcontroller-based dynamic RPM control effectively optimizes drying processes with high precision and energy efficiency. This system is highly applicable to raw-material processing industries that require stable environmental control to minimize product damage and reduce power consumption.